The variable prosodic parsings of Nivaĉle glottal stop - Gutiérrez, Analía (2016)
This paper establishes the featural and prosodic representations of the Nivacle (Mataguayan)glottal stop. On the one hand, it is proposed that the Nivacle glottal stop is unspecified for place features, but specified for constricted glottis ([c.g]). On the other hand, it is advanced that /ʔ/ is an independent consonantal phoneme in the language that has multiple prosodic parsings. First, a glottal stop can occur (contrastively) in syllable onset position. Second, a postvocalic glottal stop can be variably parsed to the vocalic Nucleus of the syllable and hence form part of a Complex Nucleus or to the coda position. As a result, two different manifestations of phonetic glottalized vowels are realized: creaky/rearticulated and vowel-glottal coda, respectively. It is argued that these diverse glottal realizations are rooted in a set of prosodic constraints.